Tradução, adaptação cultural e validação da versão brasileira da escala The Multidimensional Individual and Interpersonal Resilience Measure - Jéssica Diniz Rodrigues Ferreira (2019)
Introduction: Older adults often experience a series of non-normative and age-related changes ranging from everyday challenges to highly stressful experiences that can impact not only an individual but the whole family or social system that surrounds them. The concept of resilience is part of a set of protective factors or processes, which, despite the process of decline in physical, cognitive functions and psychosocial changes, favors the characterization of a healthy or successful aging. Objective: The proposal of this project is to add to the scientific literature new studies on the concept of resilience applied to the Brazilian context, consolidating the evidences about the processes already correlated to this construct and contributing to the operationalization of the instrument The Multidimensional Individual and Interpersonal Resilience Measure (MIIRM) through the process of translation, cultural adaptation and validation. Method: After the initial translation of the original instrument from English into Brazilian Portuguese, the pre-final version of the scale underwent cultural adaptation procedures, including expert consensus meetings and a pilot study, to verify preliminary results of scale application in the target population. Individuals over 60 years old, of both sexes, with different levels of schooling and sociodemographic profiles participated in the interviews. After this pilot study and consensus among the principal investigators, the Brazilian Version of the Individual and Interpersonal Resilience Scale (EMRII-BR) was defined, which was then submitted to the validation study. Results: The process of translation and cultural adaptation led to an instrument in Brazilian Portuguese, equivalent to the original instrument in semantic, idiomatic, experiential and conceptual terms. The final version was applied to a total of 187 elderly people. The exploratory factorial analysis (AFE) generated a model of five factors, with good fit indices (RMSEA = 0.030; TLI = 0.959; X² = 151.590 p> 0.05). The scale was consistent, with Cronbach's α of 0.705 and good test-retest reliability (ICC=0.835). No statistically significant correlation was found between resilience and the sociodemographic and epidemiological variables evaluated. Conclusion: This study demonstrated that EMRII-BR is valid and reliable for measuring resilience in the elderly.